Hubungan Kemampuan Membaca Al-Qur’an terhadap Kualitas Hafalan Al-Qur’an Juz 30 - Kania, Irna; Drajat, Manpan; Syaprudin, Didin; Mukti, Saepul; Wulandari, Dyah (Paedagogie: Jurnal Pendidikan dan Studi Islam, 2024)
In the recitation of the Quran that students read, there are some that are not based on the rules, sadly there are still students who have not been able to connect each letter. From the observation of rote juz 30, students only focus on memorizing without observing the correct reading first so that the quality of memorization is less than optimal. This study aims to describe each variable and find out how the relationship between the ability to read the Quran and the quality of memorizing the Quran in class VI MI Hudatul Ummah. Theoretical analysis used by Abdul Chaer regarding the ability to read the Quran and Misbahul Munir regarding the memorization of the Quran. The research uses a quantitative approach with the correlational method. The sample taken is all the total population of 25 respondents. The source of the data used is primary data by collecting data from observations, interviews and tests. The data analysis technique used for the hypothesis is simple correlation with Pearson. Based on the analysis of the data found: 1) The category of the ability to read the Quran of grade VI students is medium with an average value of 73.16; 2) The category of the quality of memorizing the Quran for grade VI students is medium with an average score of 75.92; and 3) The ability to the read the Quran is proven to have a relationship with the quality of memorizing the Quran even though the value of the relationship is 67.6%. Judging from the direction of the regression with a t-count value of 6.921 > 2.060, the decision was obtained by accepting Ha. The correlation value obtained is 0.822 indicating a very strong relationship.